Faktor-faktor yang Memengaruhi Anticipatory Grief pada Family Caregiver Pasien yang Didiagnosis Kanker: Narrative Literature Review - Madani, I Gusti Ayu Winda; Suarya, Luh Made Karisma Sukmayanti (PSIK FKKMK UGM, 2025)
Background: Family caregiver of patients with cancer often experience anticipatory grief (AG) when providing care. Although previous studies have explored AG in cancer contexts, most findings remain fragmented and focus only on isolated variable. Comprehensive reviews specifically examining the multifactorial determinants of AG among family caregivers of patient with cancer are limited. Objective: To synthesize recent empirical findings on the factors that influenced AG among family caregiver of cancer patients. Method: This study employed a literature review method following the PRISMA 2020 framework. Articles were searched from databases including Google Scholar, PubMed, and Sage Journals. The search terms were (